School readiness analysis to implement an inclusive education policy: A case study at elementary school - Safrizal, Safrizal; Yulia, Resti; Jumiarti, Desri (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
This study aims to describe the readiness of elementary schools in one of the sub-districts in Padang City, which includes personnel/teachers, facilities, and infrastructure, and a developmental assessment format for children with unique/inclusive needs. This research uses a descriptive quantitative method. The research subject is the elementary school Principal, which was selected using a simple random sampling technique. The research instrument used was in the form of questions packaged in a Google Form using the Guttman scale. Data were analyzed using descriptive statistics. The results showed that all schools responded well to the call for inclusive education in schools. However, the readiness of human resources, facilities, infrastructure, and several assessment systems are mostly not owned and not yet in schools. It shows that the enthusiasm for implementing inclusive education is practically not ready to be implemented considering the lack of availability of supporting facilities, both in terms of human resources and other supports.